Single-port laparoscopic appendectomy using a needle-type grasping forceps compared with conventional three-port laparoscopic appendectomy for patients with acute uncomplicated appendicitis: a single-center retrospective study. Issue 8 (August 2022) - Chen, Yang; Guo, Shigang; Liu, Yanjie; Yuan, Jieqing; Fan, Zongqi
Objective: To compare the clinical outcomes between single-port laparoscopic appendectomy using a needle-type grasping forceps (SLAN) and conventional three-port laparoscopic appendectomy (CLA) for patients with uncomplicated appendicitis. Methods: We retrospectively collected clinical data of patients with uncomplicated appendicitis who underwent SLAN or CLA from May 2019 to May 2021 in our center. The patients' baseline characteristics, perioperative outcomes, and follow-up data were compared between the two groups. Additionally, baseline characteristics were compared with postoperative outcomes in the SLAN group. Results: Ninety-six patients were enrolled (SLAN group, n = 32; CLA group, n = 64). The SLAN group had a shorter hospital stay, lower 24-hour postoperative visual analogue scale scores, shorter postoperative fasting time, lower frequency of antibiotic administration, and longer operative time than the CLA group. In the SLAN group, younger patients had a longer appendix and male patients had a thicker appendix; additionally, patients with an appendiceal diameter of 0.6 to 1.0 cm had a longer postoperative hospital stay and higher frequency of antibiotic administration. Conclusions: Compared with CLA, SLAN may be less invasive, provide faster postoperative recovery, and result in better cosmesis for patients with uncomplicated appendicitis. Further research should be performed to evaluate the long-term outcomes.